THE INFLUENCE OF LEADERSHIP AND COMPETENCE AND COMMITMENT ON JOB SATISFACTION AND WORK PERFORMANCE OF FOOD SERVICES OF KALTIM PROVINCE - Reza Fahd Adrian; Ardi Paminto; Saida Zainurossalamia ZA (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Abstract :This study aims to analyze and explain the Influence of Leadership and Competence and Commitment to Job Satisfaction and Work Performance of the Food Service of East Kalimantan Province. The sample selection technique used the Total Sampling Approach with a total sample of 76 people. Data collection techniques using questionnaires. The analysis was carried out using Partial Least Square (PLS) with the SmartPLS application version 3.8.9 and using SPSS Version 25 to test the validity and reliability of the respondents. The results showed that, leadership has a positive and significant effect on job satisfaction, the influence of competence has a positive and insignificant effect on job satisfaction, word Key : Leadership, Competence, Commitment, Job Satisfaction and Job Performance